Cerebral venous sinus thrombosis and antiphospholipid antibodies. Issue 838 (August 1995) - Boggild, M. D.; Sedhev, R. V.; Fraser, D.; Heron, J. R.
Abstract : We report two cases of cerebral venous sinus thrombosis associated with an antibody to phospholipids, namely the lupus anticoagulant. Both patients later developed further immunologically mediated conditions. The importance of screening for the lupus anticoagulant in addition to anticardiolipin antibodies in this condition and the need for follow-up of such patients is discussed.